2015
DOI: 10.1111/afe.12135
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between wild bees, hoverflies and pollination success in apple orchards with different landscape contexts

Abstract: Abstract:1. Pollination is an important ecosystem service as many agricultural crops such as fruit trees are pollinated by insects. Agricultural intensification, however, is one of the main drivers resulting in a serious decline of pollinator populations worldwide. 2. In this study pollinator communities were examined in twelve apple orchards surrounded by either homogeneous or heterogeneous landscape in Hungary. Pollinators (honey bees, wild bees, hoverflies) were surveyed in the flowering period of apple tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
70
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 73 publications
(88 reference statements)
1
70
1
6
Order By: Relevance
“…Wild bees and honey bees are important pollinators of crops (Brittain, Williams, Kremen, & Klein, ; Klein et al, ) and wild plants (Fontaine, Dajoz, Meriguet, & Loreau, ). Pollination efficiency of different crops is strongly related to wild bee species diversity (Földesi et al, ; Winfree et al, ) as well as functional diversity (Fontaine et al, ; Garibaldi et al, ). Research demonstrated that wild bees are threatened by intensive agricultural practices (Kremen, Williams, & Thorp, ) such as high pesticide application (Woodcock et al, ), and/or frequent soil tillage (Williams et al, ), which result in reduction of floral resource availability (Williams et al, ) and contribute to landscape simplification (Senapathi, Goddard, Kunin, & Baldock, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild bees and honey bees are important pollinators of crops (Brittain, Williams, Kremen, & Klein, ; Klein et al, ) and wild plants (Fontaine, Dajoz, Meriguet, & Loreau, ). Pollination efficiency of different crops is strongly related to wild bee species diversity (Földesi et al, ; Winfree et al, ) as well as functional diversity (Fontaine et al, ; Garibaldi et al, ). Research demonstrated that wild bees are threatened by intensive agricultural practices (Kremen, Williams, & Thorp, ) such as high pesticide application (Woodcock et al, ), and/or frequent soil tillage (Williams et al, ), which result in reduction of floral resource availability (Williams et al, ) and contribute to landscape simplification (Senapathi, Goddard, Kunin, & Baldock, ).…”
Section: Introductionmentioning
confidence: 99%
“…Wild bees and honey bees are important pollinators of crops (Brittain, Williams, Kremen, & Klein, 2013;Klein et al, 2007) and wild plants (Fontaine, Dajoz, Meriguet, & Loreau, 2006). Pollination efficiency of different crops is strongly related to wild bee species diversity (Földesi et al, 2015;Winfree et al, 2018) as well as functional diversity (Fontaine et al, 2006;Garibaldi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hoverflies (Diptera: Syrphidae) play important roles in providing vital ecosystem services such as pollination (Ssymank & Kearns, 2009;Petanidou et al, 2011;Jauker et al, 2012), waste decomposition (Gilbert, 1985), and biological control (White et al, 1995;Blaauw & Isaacs, 2012;Day et al, 2015). Recent studies have shown that hoverflies can serve as valuable model organisms in studies of climate change (Kaloveloni et al, 2015;Radenković et al, 2017;Miličić et al, 2018), urbanisation (Bates et al, 2011;Verboven et al, 2014), landscape structure (Power et al, 2016) or land use (Aguirre-Gutiérrez et al, 2015;Földesi et al, 2016;Lucas et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Besides honeybee, wild insects, including bumblebees, solitary bees and hoverflies, visit apple blossoms (e.g. Földesi et al 2016;Martins et al 2015;Russo et al 2017). Importantly, the abundance and diversity of wild pollinators positively affect apple yield (Földesi et al 2016;Martins et al 2015;Blitzer et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Földesi et al 2016;Martins et al 2015;Russo et al 2017). Importantly, the abundance and diversity of wild pollinators positively affect apple yield (Földesi et al 2016;Martins et al 2015;Blitzer et al 2016). These positive effects seem to be related to the additive contributions of various pollinators that differ in abundance and quality depending on their foraging patterns (Thomson and Goodell 2001;Martins et al 2015;Park et al 2016).…”
Section: Introductionmentioning
confidence: 99%